Food Resource Awareness and Information Sharing Among College Students at High Risk of Food Insecurity - Ortiz, Francisco (Curr Dev Nutr, 2020)
OBJECTIVES: To identify information dissemination needs around food resources available through the university as informed by student representing groups at risk of food insecurity. METHODS: Eight focus groups with 17 leaders of student organizations representing students at high risk of food insecurity (ie, underrepresented minorities, first generation college students, low income, foster youth, and LGBTQA+) were conducted. Students’ experiences and views regarding awareness of available food resources, barriers and facilitators to obtain information on resources, and group-specific needs to improve communication of available resources was gathered. A codebook was developed and used for inductive analysis of interview data. Deductive thematic analysis was done by engaging in extensive commentary and discussion of the code structure. RESULTS: Awareness of resources available on campus was low, especially regarding guidance on SNAP application. Although students were able to name a few available resources, they often described inaccurate details. Social networks (ie, social media, direct peer-to-peer communication) were prominently identified as relevant means to share on campus food resource information. Students often recommended coordinated marketing strategies (eg, flyers, social media presence) and direct outreach via clubs/organizations as solutions to improve resource communication. Students preferred means to receive information on how to improve food security included online content (eg, videos, mobile apps) and in person events (eg, interactive demonstrations). CONCLUSIONS: Comprehensive dissemination of available resources through relevant channels is key to improving food access, particularly among students at high risk of food insecurity. Promising dissemination strategies include direct outreach in student clubs/organizations combined with well-coordinated marketing campaigns that include a broad social media presence and online content. FUNDING SOURCES: This research is being supported by the Blum Center for Developing Economies, University of California, Merced; and the Global Food Initiative, University of California Office of the President.